Eksport zagranicznych inwestycji bezpośrednich z krajów Azji Południowo-Wschodniej a procesy integracji regionalnej - Domżalski, Sebastian (Outward foreign direct investment from Southeast Asia and regional integration, 2009)
Southeast Asian transnational companies have recently become very active in expanding their business activities (in a form of foreign direct investment) not only in the region, but also in the more remote parts of the world. The purpose of this study is to analyze the size, relevance, sources and motives of these investments, especially within the Association of Southeast Asian Nations (ASEAN) and the impact of integration process on these flows. The main thesis claims that although export of investment from Southeast Asia has increased in recent years quite rapidly it is still relatively less important than its import. Additionally, it is also substantially limited regionally
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 62-71